61 SUBVERSION OF TYPE I INTERFERON ANTIVIRAL DEFENSE IN HUMAN AIRWAY EPITHELIAL CELLS BY ADENOVIRUS INFECTION. (1st March 2007) - Shi, L.; Ramaswamy, M.; Manzel, L. J.; Look, D. C.
Abstract : A prerequisite for successful viral invasion and replication in host cells is a mechanism for avoiding antiviral defense, particularly those regulated by interferons. Therefore, viral evolution has generated mechanisms to resist host cell antiviral systems, but the biochemical basis for evasion of interferon (IFN) effects in the airway by adenoviruses is incompletely understood. To identify the molecular mechanisms for adenoviral inhibition of IFN-dependent antiviral immunity, we examined adenovirus type 5 (AdV) effects on expression of type I IFN-dependent genes and on levels and activation of Janus family kinase-signal transducer and activator of transcription (JAK-STAT) signaling components in primary cultures of human airway epithelial cells. We found that wild-type AdV infection inhibited IFN-α-induced expression of the antiviral proteins MxA, Stat1, and PKR using immunoblot analysis of cell lysates from uninfected and virus-infected airway epithelial cells. Replication-deficient AdV-d312 did not have this capacity. Similarly, using real-time RT-PCR analysis of RNA levels, we found that IFN-α-induced mRNA expression for these antiviral genes was also inhibited by AdV, suggesting that the virus caused a global blockade in type I IFN-dependent gene expression. This conclusion was confirmed when we found that infection with AdV for 12 hours or greater inhibited subsequent IFN-α-dependent phosphorylation and nuclear translocation of the Stat1 and Stat2 transcription factors that are required for activation of type I IFN-dependent genes. There was no evidence of epithelial cell injury, generation of a soluble extracellular inhibitor, or altered type I IFN receptor chain 1 or 2 cell surface expression, suggesting that viral effects were mediated inside epithelial cells. Further examination of the type I IFN-activated JAK-STAT pathway revealed that AdV infection also caused a loss of IFN-α-induced phosphorylation of the receptor-associated Jak1 and Tyk2 tyrosine kinases. This global blockade of signaling pathway activation appeared to occur through modulation of Jak1 expression by adenoviral down-regulation of Jak1 mRNA levels in epithelial cells. AdV infection inhibited other Jak1-dependent signaling cascades in airway epithelial cells, including interleukin (IL)-6-dependent phosphorylation of Stat3. In contrast, IL-4- and IL-13-dependent phosphorylation of Stat6 was not affected during AdV infection, and these pathways can function independently of Jak1, indicating that the virus modulates specific signaling pathways. Based on these and previous results, AdV inhibits type I IFN-induced gene expression through at least two mechanisms: (1) expression of the E1A oncoprotein that inhibits IFN-induced transcription factors within the first few hours of infection and (2) down-regulation of the expression of Jak1 after 12 hours of infection. These findings suggest that AdV uses multiple strategies to ensure inhibition of antiviral effects of IFN throughout the viral replication cycle to subvert the airway immune response and establish a productive infection.